Selective behavioural impairments in mice heterozygous for the cross disorder psychiatric risk gene DLG2. (3rd February 2022) - Pass, Rachel; Haan, Niels; Humby, Trevor; Wilkinson, Lawrence S.; Hall, Jeremy; Thomas, Kerrie L.
Abstract: Mutations affecting DLG2 are emerging as a genetic risk factor associated with neurodevelopmental psychiatric disorders including schizophrenia, autism spectrum disorder, and bipolar disorder. Discs large homolog 2 (DLG2) is a member of the membrane‐associated guanylate kinase protein superfamily of scaffold proteins, a component of the post‐synaptic density in excitatory neurons and regulator of synaptic function and plasticity. It remains an important question whether and how haploinsuffiency of DLG2 contributes to impairments in basic behavioural and cognitive functions that may underlie symptomatic domains in patients that cross diagnostic boundaries. Using a heterozygous Dlg2 mouse model we examined the impact of reduced Dlg2 expression on functions commonly impaired in neurodevelopmental psychiatric disorders including motor co‐ordination and learning, pre‐pulse inhibition and habituation to novel stimuli. The heterozygous Dlg2 mice exhibited behavioural impairments in long‐term motor learning and long‐term habituation to a novel context, but not motor co‐ordination, initial responses to a novel context, PPI of acoustic startle or anxiety. We additionally showed evidence for the reduced regulation of the synaptic plasticity‐associated protein cFos in the motor cortex during motor learning. The sensitivity of selective behavioural and cognitive functions, particularly those dependent on synaptic plasticity, to reduced expression of DLG2 give further credence for DLG2 playing a critical role in specific brain functions but also a mechanistic understanding of symptom expression shared across psychiatric disorders. Abstract : Haploinsufficiency of Dlg2 is a risk for common developmental neuropsychiatric disorders including autism spectrum disorder and schizophrenia. In this study of heterozygous Dlg2 male mice we show impaired motor learning and long‐term habituation to a novel context, but normal motor co‐ordination, normal PPI (despite a reduction in acoustic startle response), and normal anxiety state. The impact of the genetic lesion on the selective behavioural phenotypes associated with these neuropsychiatric disorders correlate to the reduced cortical expression of Dlg2 in these mice and cFos activation associated with learning.